2022
DOI: 10.3390/jcm11030584
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Discrimination Testing in Patients with a Voice Disorder

Abstract: Auditory perception plays an important role in voice control. Pitch discrimination (PD) is a key index of auditory perception and is influenced by a variety of factors. Little is known about the potential effects of voice disorders on PD and whether PD testing can differentiate people with and without a voice disorder. We thus evaluated PD in a voice-disordered group (n = 71) and a non-voice-disordered control group (n = 80). The voice disorders included muscle tension dysphonia and neurological voice disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Dessa forma, recursos vocais favorecerão a liberdade de interpretação. Além disso, a autoavaliação vocal está associada com a percepção auditiva e estudos têm verificado que a disfonia comportamental pode estar relacionada a distúrbios do processamento auditivo (26,27) .…”
Section: Discussionunclassified
“…Dessa forma, recursos vocais favorecerão a liberdade de interpretação. Além disso, a autoavaliação vocal está associada com a percepção auditiva e estudos têm verificado que a disfonia comportamental pode estar relacionada a distúrbios do processamento auditivo (26,27) .…”
Section: Discussionunclassified
“…Thereby, vocal resources might favor the freedom of interpretation. In addition, vocal self-evaluation is associated with auditory perception and studies have found that behavioral dysphonia might be related to disorders of auditory processing (26,27) .…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical and physiological structures that lead to an enormous number of variations in vocal harmonies create an individual vocal identity and personality, which are unique to each person. The social contexts of the voice, i.e., voice frequencies that are connected to social positions and human perception, are derived from these vocal identities, as they constantly transmit information about the speaker, especially in different social contexts, beyond the textual contents and the context of the social encounter (Karagkouni, 2021;Nguyen et al, 2022). Other studies confirm that voice triggers a signal for human attractiveness and social dominance.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 98%